Effect of different types of mulches on growth and yield of drip irrigated vegetables - E. B. GILSHA BAI; Dr. Jobi V. Paul (Guide) (Tavanur 1997 Kelappaji College of Agricultural Engineering and Technology)
Effect of different types of mulches on growth and yield of drip irrigated vegetables
Effect of different types of mulches on growth and yield of drip irrigated vegetables